Three-dimensional accuracy of partially guided implant surgery based on dental magnetic resonance imaging - Schwindling, Franz Sebastian; Jürchott, Alexander; Boehm, Sophia; Rues, Stefan; Kronsteiner, Dorothea; Heiland, Sabine; Bendszus, Martin; Rammelsberg, Peter; Hilgenfeld, Tim (Clinical oral implants research, 2021)
Objectives To measure in vivo 3D accuracy of backward-planned partially guided implant surgery (PGIS) based on dental magnetic resonance imaging (dMRI). Material and Methods Thirty-four patients underwent dMRI examinations. Tooth-supported templates were backward planned using standard dental software, 3D-printed, and placed intraorally during a cone beam computed tomography (CBCT) scan. Treatment plans were verified for surgical viability in CBCT, and implants were placed with guiding of the pilot drill. High-precision impressions were taken after healing. The 3D accuracy of 41 implants was evaluated by comparing the virtually planned and definitive implant positions with respect to implant entry point, apex, and axis. Deviations from the dMRI-based implant plans were compared with the maximum deviations calculated for a typical single implant. Results Twenty-eight implants were placed as planned in dMRI. Evaluation of 3D accuracy revealed mean deviations (99% confidence intervals) of 1.7 ± 0.9mm (1.2-2.1mm) / 2.3 ± 1.1mm (1.8-2.9 mm) / 7.1 ± 4.8° (4.6-9.6°) for entry point / apex / axis. The maximum deviations calculated for the typical single implant surpassed the upper bounds of the 99% CIs for the apex and axis, but not for the entry point. In the 13 other implants, dMRI-based implant plans were optimized after CBCT. Here, deviations between the initial dMRI plan and definitive implant position were only in part higher than in the unaltered group (1.9 ± 1.7 mm [0.5-3.4 mm] / 2.5 ± 1.5 mm [1.2-3.8 mm] / 6.8 ± 3.8° [3.6-10.1°] for entry point / apex / axis). Conclusions The 3D accuracy of dMRI-based PGIS was lower than that previously reported for CBCT-based PGIS. Nonetheless, the values seem promising to facilitate backward planning without ionizing radiation.